UPAYA PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN PAPAN HURUF - Gunawan Agustian; Arsyi Rizqia Amalia; Dyah Lyesmaya; Luthfi Hamdani Maula (LPPM STKIP Bina Bangsa Meulaboh, 2024)
The aims of this study were: (1) to explain how early reading learning was carried out by using letter boards, and (2) to describe how students' initial reading skills were improved by using letter boards. Classroom action research (CAR) is the research approach used. The research process requires four steps to be completed in each cycle: (1) planning; (2) action; (3) observation; and (4) reflection. Class 1C SDS Darul 'Amal Jampangkulon participated in two cycles of this research. The pre-cycle student learning outcomes were still low, only 25% or 5 students were fluent at beginning reading. In cycle I, students' ability in beginning reading skills increased by 50%, with 10 scoring fluent and 10 scoring non-fluent. and 15% is still not current.